PENGARUH ISI PESAN KESEHATAN MENTAL INSTAGRAM RILIV TERHADAP KEMAMPUAN RESILIENSI (Survei Terhadap Followers Instagram Riliv): Mental Health Messages, Resilience Ability, Instagram Followers, Riliv - Ramadhanty, Hanna Azizah; S.S, M.A., Tsuroyya (Universitas Negeri Surabaya, 2023)
This research aims to empirically examine the effect of the contents of Riliv's Instagram mental health messages on the resilience abilities of Instagram followers through a quantitative approach and survey methods. The analysis of this study uses an independent variable, namely the contents of Riliv's Instagram mental health messages and the dependent variable is the resilience of Instagram followers. The research sample is Riliv's active Instagram followers using the purposive-sampling method. Data collection was carried out by distributing 400 questionnaires. The statistical method used is simple regression analysis and partial statistical test (T-test) as a research hypothesis test. The results of this study indicate that the contents of Riliv's Instagram mental health messages have an effect on the resilience ability of followers. This is based on the results of the hypothesis test, where the t-count value is 3.185 greater than the specified t-table value of 0.1966 and when viewed from the significance figure the results are 0.000 < 0.05.